Influence of dystonia on the response to long-term L-dopa therapy in Parkinson's disease. Issue 4 (August 1973) - Andrews, Colin J.
Abstract : The gait of normal subjects was examined electromyographically and the pattern was altered during preferential blockade of large nerve fibres to alternating activity in flexor and extensor muscles. The EMG activity was disrupted more in flexor than extensor muscles by preferential ischaemic blockade. Normal gait was associated with flexor contraction only when the foot was lifted and placed on the ground, whereas during ischaemic blockade flexor contraction continued during the interval between foot lifting and foot placement. The `freezing' or `blocking' gait in Parkinson's disease was found to be associated with coactivation of flexor and extensor muscles and this phenomenon occurred only in patients with features of flexion dystonia in the electromyographic recordings of their tonic stretch reflexes. Eight of nine patients with evidence of flexion dystonia showed a deterioration in their response to l -dopa therapy over a two year period, whereas four patients without flexion dystonia maintained their clinical improvement.